Hydroliza w biodegradacji odpadów organicznych = Hydrolysis in biodegradation of organic waste - Myszograj, Sylwia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the basic mathematical description of the hydrolysis reaction of organic substrates. It was examples of enzymatic hydrolysis (kh) and biodegradation (kb) constant values for sewage sludge and for selected waste summarized.
Keywords: hydroliza; osady ściekowe; odpady komunalne; hydrolysis; sewage sludge; municipal waste